Perancangan Media Informasi Augmented Reality Wihara Kstigarbha Bodhisattva Tanjungpinang - Handayani, Nadhila; Sudiani, Yoni; Rajab, Junaidi (Journal of Tourism Sciences, Technology and Industry, 2024)
Ksitigarbha Bodhisattva Temple is a place of Buddhist worship and has become a religious and cultural tourist spot in the Riau Islands, Tanjungpinang. The statues at the Ksitigarbha Bodhisattva Temple only display information in Mandarin, even though the tourists who visit there mostly come from outside the area, not even just Buddhists. From interviews with visitors who came to the temple, they stated that apart from getting interesting photos, they also wanted to know what the Ksitigarba Bodhisattva Temple was like. However, due to the lack of communicative information, tourists do not know the information written in Mandarin. So "Designing Augmented Reality Information Media for the Ksitigarbha Bodhisattva Tanjungpinang Temple" was created. The data collection methods used were observation, interviews and literature study. The data analysis method used is SWOT and is aimed at a general target audience of all ages who like to seek new insights and also people who like to visit cultural and religious tourist attractions. After collecting these data, we proceed to the brainstorming stage of creating the work, namely compiling visual and verbal concepts on the designed information media. The results of this design are in the form of Augmented Reality, infographics, e-books, merchandise.